Contribution of solid and liquid fractions of sewage sludge pretreated by high pressure homogenization to biogas production. (August 2019) - Nabi, Mohammad; Zhang, Guangming; Zhang, Panyue; Tao, Xue; Wang, Siqi; Ye, Junpei; Zhang, Qian; Zubair, Muhammad; Bao, Shuai; Wu, Yan
Graphic abstract: Highlights: Effect of HPH pretreatment on sewage sludge was evaluated under different pressures. Methane was mainly produced from sludge solid fraction. Increase of methane yield was due to organic release and sludge floc disruption. There are synergistic effect between sludge solid and liquid for methane production. Abstract: High pressure homogenization (HPH) pretreatment can effectively enhance anaerobic sludge digestion. In order to understand the corresponding mechanisms, different homogenization pressures were applied on sewage sludge, and solid and liquid fractions were separately digested to clarify contribution of solid and liquid fractions to biogas production. Results showed that the methane was mainly produced from solid fraction, and methane yield was increased with the increase of pretreatment pressure. The biogas and methane production from sludge (digested without solid–liquid separation) was 17% and 45% higher than the sum of that from solid and liquid fractions (digested separately) under a pressure of 40 MPa, respectively. This indicated that the sludge liquid fraction synergistically improved the biodegradation of sludge solids. The improvement of anaerobic digestion was attributed to organic release by sludge disintegration, sludge disruption and further increase of particle surface area. The methane production was linear with effectiveness of HPH pretreatment.